A Characterization of Robust Regions of Attraction for Discrete-Time Systems Based on Bellman Equations. Issue 2 (2020) - Xue, Bai; Zhan, Naijun; Li, Yangjia
Abstract: In this paper we present a Bellman equation for computing robust regions of attraction for state-constrained perturbed discrete-time systems. The robust region of attraction of interest is a set of states such that every trajectory initialized in it will approach an equilibrium while never violating a specified state constraint, regardless of the actual perturbation. In this approach, the interior of the maximal robust region of attraction is characterized as the strict one sub-level set of the unique bounded and continuous solution to a Bellman equation.